Reflections on the proceedings of the 19th Congress of the Chinese Communist Party (CCP) on Sino-Africa and Sino-BRICS relations (The Strategic Review for Southern Africa, 2021)
Beijing’s economic diplomacy has, since the dawn of the millennium, sought to reconfigure the world by championing a new economic order that is predicated on the principles of multipolarity and fairness. The last policy conference of the Chinese Communist Party (CCP) shed some light into how these policy ideals are to be carried out by Beijing and how they will bear on her relationship with countries from the Global South. This paper considers the policy statements of the CCP during its 19th congress held in October 2017 as a sneak peek into the future of China’s economic diplomacy and the implications for Africa’s own economic future from the context of Brazil, Russia, India, China and South Africa (BRICS). It argues that China’s role as the leader of the BRICS fulcrum reflects her goal to have a global influence that will see erstwhile economic backwaters such as Africa turning their focus away from the West to the East in search of sustainable solutions to their economic challenges.Keywords: China, economic diplomacy, multi-polarity, BRICS, Chinese Communist Party